Examination of skin-fermented natural wines - Bene, Zsuzsanna; Oláhné-Horváth, Borbála; Kneip, Antal; Balling, Péter (Élelmiszervizsgálati Közlemények, 2022)
The ancient white wine making technology, the “qvevri”, is gaining more and more attention among consumers, not only because it is unique and special, but also because sustainability and closeness to nature are fundamental characteristics of this winemaking process. All of this is demonstrated by the fact that this ancient Georgian process using traditional clay vessels was added to the UNESCO List of Intangible Cultural Heritage of Humanity in 2013, and in 2020, The International Organisation of Vine and Wine (OIV) included skin-fermented white wine in the category of special wines. This wave is also present in Hungary, since “natural” wine and “orange wine” have already appeared in a 2021 law as „Other restricted terms”. The essence of the winemaking process is skin-contact fermentation and microoxidation, for which a number of vessels can be used: amphoras or qvevris, ceramic eggs or spin barrels, as a function of which the chemical composition of the wines may vary, as well as the formation of the precursor compounds of the aroma components. In this study, natural wines produced in the Tokaj wine region, using amphoras and ceramic egg vessels were examined.